Biomechanical comparison of the vertical jump test and push jerk exercise - Chochon, S. R. (1994)
The purpose of this study was to compare kinematic variables between vertical jump tests (VJ) and push jerks (PJ), both performed with (CM) and without (S) counter movement, to identify possible similarities. Ten basketball players and 10 weightlifters performed SVJ, CMVJ, and SPJ and CMPJ at 60%, 75%, and 90% of one repetition maximum. Power outputs and ankle, knee, and hip joint peak angular velocity and acceleration mean values were significantly ($p < .05$) higher for VJ than PJ. Angles at these joints at peak angular velocity tended to be similar for VJ and PJ. Occurrence of peak angular velocity for the knee and hip joints occurred within one video field (16.7 ms) for the VJ and PJ. Results of this investigation provide evidence for similarities between the movement patterns of VJ and PJ. Thus, use of the PJ exercise may improve performance in the VJ test (training specificity).